Management of Mammae Tumor Cases in Mixed Chow Dog Breeds at Makassar Zoo Clinic (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2021)
Tumors are a common problem in many types of dogs, including chow-chows and their breeds. This disease is a degenerative diseases resulting from mammary gland cells dividing and growing without control. The clinical signs that are seen are usually the presence of a slow mass growth, single or multiple. Treatment of mammary tumor patients in mixed chow dogs at the Makassar Zoo Clinic used ovariohysterectomy and simple mastectomy methods. Premedication of 0.025% Athropine sulphate with dos e 0.04 mg/kg BW subcutaneous route, 10% anesthetic Ketamine HCl dose of 15 mg / kg BW and Xylasine 2% dose 2 mg / kg BW intramuscular route. In addition, it is continued with supportive therapy in the form of giving Be tamox LA, Meloxicam, and more attention to post operative management such as feeding and post operative wound management.